Can Entrepreneurship Be Measured? - Alshaik, Ziad R. (International Review of Management and Marketing, 2018)
The research paper groups entrepreneurship as either conceiving or performing. Some arguments performing entrepreneurship can be measured while conceiving entrepreneurship cannot. In conceiving entrepreneurship, the concepts and thoughts of doing business can be observed. Performing entrepreneurship is the real application of these thoughts and ideas, which can be measured by outlining the trail or footsteps of the entrepreneur (Foss & Klein, 2005). This paper shows that several sign measures of performing entrepreneurship can be selected by applying the confirmatory factor assessment under the approach of latent-variables sculpting. Keywords: Entrepreneurship, Measuring Entrepreneurship, Performing Entrepreneurship JEL Classifications: O3, O31, O310